Liver ailments in pregnancy: our experience - Kohli, Uttara Aiyer; Seth, Atul; Singh, Sanjay; Mishra, Rajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The spectrum of liver disease is varied and is associated with increased maternal and perinatal morbidity and mortality when pregnancy coexists with the liver disease. This study aims to analyze the incidence, spectrum, clinical presentation and outcome of liver diseases complicating pregnancy Methods: A retrospective cohort study was conducted and data was collected from the hospital records of obstetric cases diagnosed with liver disease complicating pregnancy in a tertiary care hospital, over a period of two years. Results: A total 146 cases of liver diseases complicating pregnancies were recorded out of 5018 deliveries (2.9%). Intrahepatic cholestasis of pregnancy (n=52, 35.62%) and severe preeclampsia (n=47, 32.19%, with HELLP n=8, 5.48%) accounted for majority of cases. The incidence of chronic hepatitis B infection was 20.56% (n=30). There were two maternal deaths (1.37%) attributed to severe post-partum HELLP and severe preeclampsia with multi organ failure. Conclusions: Liver diseases in pregnancy have a non-specific presentation and may be associated with a wide range of conditions, early diagnosis and timely appropriate intervention can help reduce the mortality and morbidity.